KAJIAN PERLUASAN KUALIFIKASI MAKNA BARANG DALAM YURISPRUDENSI HUKUM PIDANA BELANDA DAN INDONESIA DI ERA SIBER - Hardinanto, Aris; Barda Nawawi Arief; Setiyono, Joko (Faculty of Law, Universitas Pasundan, 2024)
The development of information technology, especially the internet, has affected criminal law. One of the resulting impacts is the qualification of goods in the cyber era. The development of criminal law in the Netherlands, particularly the Criminal Code, related to information technology is progressive regarding the qualification of goods, including cases related to the interpretation of goods in cyberspace by the Supreme Court of the Netherlands. This article argues that Dutch criminal law has repeatedly extended the qualification of the meaning of goods related to cybercrime through the jurisprudence of the Supreme Court of the Netherlands. The expansion of the qualification of goods in Dutch criminal law contextually includes account balances, online gaming features, and credit. Indonesian jurisprudence has once expanded the scope of goods in deciding account balance cases. The extension of the qualification of goods, including computer data in the National Criminal Code, based on problematic decisions of the Arnhem High Court in the Netherlands, is contradictory to the spirit of national criminal law reform. Keywords: Qualification, Goods, Criminal Law.